Late paleozoic–mesozoic subduction and accretion of the paleo-pacific plate: insights from the ocean plate stratigraphy of the wandashan accretionary complex, NE China. Issue 1 (2nd January 2023) - Liang, Yong; Zheng, Han; Li, Huan; Förster, Michael W.; Li, Zhihan
ABSTRACT: The Wandashan accretionary complex (AC) is located in the easternmost part of Northeast China and consists of the Raohe complex in the east and Yuejinshan complex in the west. It represents an excellent location for insights into Paleo-Pacific subduction and accretion processes. However, the protolith (mainly contains Ocean Plate Stratigraphy 'OPS' and ophiolite) nature and tectonic evolution of the Wandashan AC are under debate. This contribution reports three representative geological sections, conducts the OPS reconstruction, compares the reconstructed Wandashan OPS with the adjacent Bikin OPS in Russia and Inuyama–Mino–Neo OPS in Japan, and re-accessed detrital zircon U-Pb age data of the Wandashan area. The results show that the protolith of the Yuejinshan complex is consistent with the OPS formed on a back-arc basin. This back-arc basin formed in the Early Permian and eventually closed after 216 Ma, and the basin materials emplaced and metamorphosed at 210–180 Ma to form the metasedimentary rocks and greenschists. The Raohe complex has a relatively complete OPS, which mainly includes Carboniferous–Permian coastal- to shallow-sea- limestones, Middle Triassic–Early Jurassic pelagic cherts, Middle Jurassic hemipelagic siliceous shales/mudstones and slates, and a Middle Jurassic–Early Cretaceous turbidite sequence. The provenances of the trench fill (turbidites) include the widespread Precambrian basement in NE China, the Yuejinshan complex, seamounts and seafloor sediments on the subducted slab, and the adjacent Jiamusi, Khanka, and Songnen massifs. The Raohe OPS experienced decollement, submarine sliding, diapirism, offscraping, underplating, out-of-sequence thrusting, and progressive disruption during the process of accretion, forming the Raohe complex in the Middle Jurassic–Early Cretaceous ( 169–133 Ma). Together, the Raohe and Yuejinshan complexes form the Wandashan AC.